2017
DOI: 10.1159/000484258
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Stimulated Genes as Enhancers of Antiviral Innate Immune Signaling

Abstract: The ability of a host to curb a viral infection is heavily reliant on the effectiveness of an initial antiviral innate immune response, resulting in the upregulation of interferon (IFN) and, subsequently, IFN-stimulated genes (ISGs). ISGs serve to mount an antiviral state within a host cell, and although the specific antiviral function of a number of ISGs has been characterized, the function of many of these ISGs remains to be determined. Recent research has uncovered a novel role for a handful of ISGs, some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 50 publications
(80 reference statements)
1
119
0
1
Order By: Relevance
“…Type I interferons (IFN-I) bind to IFN (IFN-α/β) receptors on the surface of NK cells to prime, activate and initiate mechanisms for the destruction of infected cells. The subsequent stimulation of the IFN signalling pathway results in the increased expression of several interferon stimulated genes (ISGs) which have direct and indirect antiviral activities (1).…”
Section: Introductionmentioning
confidence: 99%
“…Type I interferons (IFN-I) bind to IFN (IFN-α/β) receptors on the surface of NK cells to prime, activate and initiate mechanisms for the destruction of infected cells. The subsequent stimulation of the IFN signalling pathway results in the increased expression of several interferon stimulated genes (ISGs) which have direct and indirect antiviral activities (1).…”
Section: Introductionmentioning
confidence: 99%
“…During virus infection, the host responds by triggering a variety of signaling cascades, especially those involved in the immune response. The activation of these pathways such as the antiviral and pro-inflammatory signaling pathways leads to the induction of an antiviral state that helps the host repress virus replication and clear the virus [27]. In turn, viruses have developed mechanisms to modulate and impair these responses, and often utilize multiple strategies to target these signaling cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported that ISGs that are induced upon MAVS activation may establish a positive-feedback loop to potentiate the antiviral signaling at multiple steps (Crosse et al, 2018). For example, the ISG protein DDX60 is an RNA helicase that, upon binding with double-strand RNA, associates with RIG-I, MDA5, and LGP2, and increases MAVS activation (Miyashita et al, 2011).…”
Section: Regulation Of Mavs Signaling By Protein-protein Interactionmentioning
confidence: 99%